STUDY OF FRACTIONATION CAPACITY ADDITION ON TOXOID TETANUS PURIFICATION USING FRACTIONAL FACTORIAL DESIGN - Gunadi, Gugun
BFM is a pharmaceutical company that that produces purified tetanus toxoid. The demand for BFM’s purified tetanus toxoid will continue to increase until 2022, while the occupied production capacity in 2018 has reached 82%. One effort to increase the production capacity of purified tetanus toxoid is fractionation capacity addition on purification process. This study aims to determine and analyze the influential factors and interactions that affect the yield and purity as a quantitative response to the fractionation process. The results of the analysis were used as a evaluating basis for plans of fractionation capacity addition in the process of tetanus toxoid purification. Influential factors are determined by the fishbone and failure mode and effect analysis (FMEA) methods. The fractional factorial of design of experiments was carried out on four influential factors, namely: titers, sedimentation time, centrifugation time, and centrifugation speed. The response of yield and purity in the design of experiments was analyzed using analysis of variance (ANOVA), pareto graph, factorial plots, and response optimizer. The results of the analysis show the four factors and their interactions have a significant effect (p-value <0.05), have a positive effect, and the curvature relationship is significant towards the yield. Titers, centrifugation times and their interactions, and interactions between titers with centrifugation speed have a significant effect (pvalue <0.05), have a positive effect, and curvature relationships are not significant for purity. All experimental treatments produce products according to the specifications of purified tetanus toxoid. Based on fractional factorial analysis, the the capacity addition of the tetanus toxoid purification process can be done by fractionation of concentration titer at a 3000 Lf/ml. With the increase in the capacity of the fractionation process, actual production capacity will increase by around 1.5 times the dose and the occupied production capacity decreases to 55%.